Three-dimensional OCT based guinea pig eye model: relating morphology and optics - Pérez-merino, Pablo (Biomed Opt Express, 2017)
Custom Spectral Optical Coherence Tomography (SOCT) provided with automatic quantification and distortion correction algorithms was used to measure the 3-D morphology in guinea pig eyes (n = 8, 30 days; n = 5, 40 days). Animals were measured awake in vivo under cyclopegia. Measurements showed low intraocular variability (<4% in corneal and anterior lens radii and <8% in the posterior lens radii, <1% interocular distances). The repeatability of the surface elevation was less than 2 µm. Surface astigmatism was the individual dominant term in all surfaces. Higher-order RMS surface elevation was largest in the posterior lens. Individual surface elevation Zernike terms correlated significantly across corneal and anterior lens surfaces. Higher-order-aberrations (except spherical aberration) were comparable with those predicted by OCT-based eye models.